2016
DOI: 10.3892/ijo.2016.3515
|View full text |Cite
|
Sign up to set email alerts
|

PAX8 is transcribed aberrantly in cervical tumors and derived cell lines due to complex gene rearrangements

Abstract: The transcription factor PAX8, a member of the paired box-containing gene family with an important role in embryogenesis of the kidney, thyroid gland and nervous system, has been described as a biomarker in tumors of the thyroid, parathyroid, kidney and thymus. The PAX8 gene gives rise to four isoforms, through alternative mRNA splicing, but the splicing pattern in tumors is not yet established. Cervical cancer has a positive expression of PAX8; however, there is no available data determining which PAX8 isofor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…In the present study, MSK2 and PAX8 expression levels were positively correlated in tumor cells, which was expected since there is a correlation between PAX8 and CREB1 as well as ATF1, which triggers cell proliferation and transformation . Moreover, PAX8 regulates cell proliferation and is frequently abnormally activated in SCC . According to previous reports, PAX8 can regulate E2F1 and affect the phosphorylation of RB, to then regulate the sequential target genes related to tumor cell proliferation, survival, and migration .…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In the present study, MSK2 and PAX8 expression levels were positively correlated in tumor cells, which was expected since there is a correlation between PAX8 and CREB1 as well as ATF1, which triggers cell proliferation and transformation . Moreover, PAX8 regulates cell proliferation and is frequently abnormally activated in SCC . According to previous reports, PAX8 can regulate E2F1 and affect the phosphorylation of RB, to then regulate the sequential target genes related to tumor cell proliferation, survival, and migration .…”
Section: Discussionsupporting
confidence: 72%
“…14 Moreover, PAX8 regulates cell proliferation 32,33 and is frequently abnormally activated in SCC. 34,35 According to previous reports, PAX8 can regulate E2F1 and affect the phosphorylation of RB, to then regulate the sequential target genes related to tumor cell proliferation, survival, and migration. 36 When MSK2 was knocked down in tumor cells, cell proliferation, viability, tumor volume, and tumor weight were all reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it has been reported that several novel PAX8 transcripts can be observed in cervical carcinoma, indicating differential regulation properties during carcinogenesis (44).…”
Section: Discussionmentioning
confidence: 99%
“…miRs are thought to act as a negative regulator of a large number of genes through interaction with the 3′-untranslated regions (3’-UTR) of target mRNAs [ 6 ]. Pax8 is aberrantly expressed in several cancer types including papillary thyroid carcinoma [ 7 ], cervical tumors [ 8 ], and glioblastoma [ 9 ]. Overexpression of PAX8 has a poor prognostic impact on patients with endometrial cancer [ 10 ].…”
Section: Introductionmentioning
confidence: 99%